The testing of the effect of belief-adjustment model and framing effect on investment decision making by using long series account-ing information - Rika Nur Aftari Latief (The Indonesian Accounting Review, 2017)
The objective of this research is to examine the differences in investment decisions made by non-professional investors when the information provided is presented in some differ-ent ways. Belief-adjustment model (information order and disclosure pattern) and fram-ing effect are pretended in some factors, which influence investors to make different deci-sions. Design of experiment for this research is 2×2×2. Participants involved in this research are 111 undergraduate students of STIE Perbanas Surabaya majoring in Ac-counting and Management. The statistical method used in this study is independent sample t-test or mann-whitney u-test. The results show that either step-by-step or end-of-sequence presentation patterns can cause recency effect, and it is greater for sequential condition than simultaneous condition. But, the result is inconsistent for end-of-sequence pattern which in some conditions can caused no order effect. In another side, the result also proves that framing effect can influence investor’s consideration in deci-sion making.